The Influence Of Self-Reflection, Certified Independent Study Internship Experience (MSIB), And Self-Efficacy On The Work Readiness Of Riau University Students - Rahmat Junaidi; Rosnelly Roesdy; Zuhroh Mahdalena; Abd. Rasyid Syamsuri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The Ministry of Education, Culture, Research, and Technology and the University of Riau provide a number of excellent programs, including the certified independent study internship program (MSIB), to students in an effort to meet one of the government's objectives, which is to increase the competency of superior human resources. This study aims to determine the effects of self-reflection, certified independent study internship experience (MSIB), and self-efficacy on the work preparedness of Riau University students. The study's participants were those who took part in MSIB batch 6 activities. The complete research sample consisted of the 122 responders from batch 6 using the Purposive Sampling approach. The results of the study show that self-efficacy, self-reflection, and the MSIB internship experience all have an impact on the work readiness of Riau University students. Additionally, self-efficacy, self-reflection, and the MSIB internship experience all have an impact on self-efficacy.